Antithrombotic Treatment for Left Ventricular Assist Devices: One Does Not Fit All - Scala, Emmanuelle; Othenin-Girard, Alexandra (Hämostaseologie, 2025)
As the prevalence of heart failure is increasing globally, left ventricular assist devices (LVADs) have become essential therapeutic options in managing advanced heart failure. This review explores the development of LVAD technology, with a focus on the shift from pulsatile to continuous-flow devices, particularly the HeartMate 3, the most advanced generation of LVADs. The evolution in design has significantly enhanced patient survival and quality of life. However, hemocompatibility-related adverse events (HRAEs)—such as pump thrombosis, ischemic and hemorrhagic strokes, and gastrointestinal bleeding—remain major clinical challenges. Striking the delicate balance between preventing thromboembolic events and minimizing hemorrhagic risks remains critical in LVAD patient management. Current therapeutic strategies typically involve long-term anticoagulation with vitamin K antagonists and antiplatelet therapy, though optimal management must be individualized based on patient-specific factors and device characteristics. Emerging alternatives, including low-dose anticoagulation, direct oral anticoagulants such as apixaban, and aspirin-free regimens, offer promising potential to reduce adverse outcomes. This review also highlights the role of innovative mechanical designs in minimizing shear stress and alternative treatments in preventing complications like gastrointestinal bleeding. Despite these advancements, personalized treatment strategies are critical, as no single therapeutic regimen fits all LVAD recipients. Ongoing research into both device technology and pharmacological therapies is essential to further reduce HRAEs and improve long-term outcomes for LVAD patients.
Keywords: left ventricular assist device; hemocompatibility-related adverse event; antithrombotic treatment; antiplatelet therapy